Peran Pendidikan Islam Berbasis Pesantren Dalam Membangun Karakter Religius Siswa di MA NU TBS Kudus - Yusuf, Bahrudin; Al Rosid, Moh. Harun (Media Manajemen Pendidikan, 2025)
This study explores the role of Islamic education based on Islamic boarding schools in shaping the religious character of students at MA NU TBS Kudus. Using a qualitative descriptive approach, data were gathered through interviews with eight purposively selected informants, participatory observation, and documentation. The findings reveal that the integration of formal curriculum and pesantren-based religious practices—such as yellow book study, congregational prayers, dhikr, and daily wirid—significantly contributes to students' religious character development. The presence of kiai and teachers as daily role models reinforces students' internalization of Islamic values. Additionally, structured worship routines enhance students' discipline, persistence, and commitment to religious life. Supported by Thomas Lickona’s character education theory and B.F. Skinner’s reinforcement theory, the study concludes that the MA NU TBS Kudus model effectively combines cognitive, affective, and behavioral aspects of religious character education. This integrated approach presents a holistic and replicable framework for other Islamic educational institutions seeking to strengthen students’ moral and spiritual development.